Mineralogia e aspectos gemológicos do diamante da região do Rio Borrachudo (Tiros, MG) - Luis Alberto de Deus Borges (2013)
The region of Rio Borrachudo, Tiros - MG is inserted in a diamond province of Minas Gerais. Although this region has been little studied, several reports of diamonds motivate us to do a more detailed research of both the mineralogy and for the possible primary sources of this region. Diamonds found in the alluvial of the Borrachudo River have excellent gemological quality, with high degree of purity and a color pattern of high commercial value. The size is limited, ranging from 0.10 to 0.30 ct, but there is a presence of giant stones. Through texture and morphological characterizations of the diamonds it is concluded that they had high dissolution, with the chips, flats, octahedral and its descendents (rhombic dodecahedrons) forms being found. The abrasion study indicates little mechanical wear to the superficial displacement, suggesting that the primary sources are in close proximity. The comparison with diamonds found in two different locations in the Abaeté River, Bombas and Fortaleza, allowed us to find significant differences between diamonds from the three locations. The texture of those diamonds surface indicates the same sequence of formation and dissolution events for the three areas, suggesting they had undergone the same processes. The study of primary sources was not conclusive, but the study of the indicator minerals indicates these sources. The presence of "rocks" in the midst of siltstones of the Bambuí Group with discordant structure and differentiated mineralogy, suggests the need for further research in these regions.